2016
DOI: 10.1016/j.ttbdis.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Detection and phylogenetic characterization of Theileria spp. and Anaplasma marginale in Rhipicephalus bursa in Portugal

Abstract: a b s t r a c tTicks are obligatory blood-sucking arthropod (Acari:Ixodida) ectoparasites of domestic and wild animals as well as humans. The incidence of tick-borne diseases is rising worldwide, challenging our approach toward diagnosis, treatment and control options. Rhipicephalus bursa Canestrini and Fanzago, 1877, a two-host tick widely distributed in the Palearctic Mediterranean region, is considered a multi-host tick that can be commonly found on sheep, goats and cattle, and occasionally on horses, dogs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…Here, the DNA of A. marginale was amplified from two engorged female ticks removed from cattle infected by A. marginale. Previous studies have reported A. marginale from R. bursa removed from cattle in Portugal [34], and from Iberian red deer and European wild boar in Spain [37]. It is likely that the presence of A. marginale DNA in these two ticks was due to the presence of this pathogen in the blood meal.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Here, the DNA of A. marginale was amplified from two engorged female ticks removed from cattle infected by A. marginale. Previous studies have reported A. marginale from R. bursa removed from cattle in Portugal [34], and from Iberian red deer and European wild boar in Spain [37]. It is likely that the presence of A. marginale DNA in these two ticks was due to the presence of this pathogen in the blood meal.…”
Section: Discussionmentioning
confidence: 90%
“…Rhipicephalus bursa was the most common tick infesting cattle in our study. This two-host species occurs in the entire Mediterranean, Adriatic and Aegean basins, including their islands, and North Africa [25, 34]. Rhipicephalus bursa prefers grassy slopes and low to medium altitude mountain slopes, as well as certain modified steppe and semi-desert environments [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intraerythocytic bacterium is transmitted primarily by R. bursa and infects sheep, goats, deer, and wild ruminants (Friedhoff 1997; Ferrolho et al 2016). In small ruminants, infection is usually subclinical, but occasionally, it can be severe, with symptoms such as anemia, hemoglobinuria, and fever (Hornok et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ticks have a significant negative impact on host species through their feeding behavior, causing direct skin and sub-cutaneous tissue damage and blood depletion, and also acting as vectors of different pathogens such as viruses, bacteria, and protozoa [1,2]. Belonging to the Ixodidae family, Rhipicephalus bursa is a multi-host tick widely distributed in the Mediterranean region having cattle, sheep, and goats as its primary hosts but can occasionally be found in wild ungulates, small mammals, or even humans [3][4][5]. This tick species is the main vector of the etiological agent of ovine babesiosis, Babesia ovis.…”
Section: Introductionmentioning
confidence: 99%